2012
DOI: 10.1159/000342131
|View full text |Cite
|
Sign up to set email alerts
|

Head Position and Expressed Emotion of Adolescents with Schizophrenia and Their Caregivers Compared to Non-Patient Controls

Abstract: Background: Family interactions with schizophrenia patients and caregivers rated as high expressed emotion (EE) are characterized by increased negative non-verbal behaviour. Head position is one important component of non-verbal behaviour and has not been examined in relation to EE before. The aim of this pilot study was to investigate the influence of caregivers' EE on the head position of adolescents with schizophrenia and their caregivers. Sampling and Methods: 15 adolescent schizophrenia patients and 17 no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0
2

Year Published

2014
2014
2014
2014

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
1
0
0
2
Order By: Relevance
“…With 41% of families rated as HEE, the results are consistent with studies by Ramsauer et al, who found HEE in 53% of affected families compared with 23.5% of control families, and Jarbin and colleagues, who found HEE in 41% of affected families (Jarbin et al, 2000;Ramsauer et al, 2013). Previous studies have found the prevalence of HEE in control groups to be considerably lower (between 0% and 38%), indicating a potentially more adverse climate in affected families .…”
Section: Key Findingssupporting
confidence: 87%
“…With 41% of families rated as HEE, the results are consistent with studies by Ramsauer et al, who found HEE in 53% of affected families compared with 23.5% of control families, and Jarbin and colleagues, who found HEE in 41% of affected families (Jarbin et al, 2000;Ramsauer et al, 2013). Previous studies have found the prevalence of HEE in control groups to be considerably lower (between 0% and 38%), indicating a potentially more adverse climate in affected families .…”
Section: Key Findingssupporting
confidence: 87%
“…Το πεδίο της έρευνας διαμορφώθηκε σύμφωνα με τις ιδιαιτερότητες που παρουσιάζει το νοσολογικό φάσμα στα παιδιά και τους εφήβους, το οποίο, όσον αφορά τις ψυχικές διαταραχές αντανακλά τη ρευστότητα των αναπτυξιακών διεργασιών σε αυτό τον πληθυσμό. Δε θα πρέπει να μας εκπλήσσει, λοιπόν, ότι σε αντίθεση με τους ενηλίκους, υπάρχουν ελάχιστες μελέτες σε σχιζοφρενικούς εφήβους (Asarnow et al 1994, Ramsauer 2000, Ramsauer et al 2012, Rund et al 1995, ενώ το ερευνητικό ενδιαφέρον στρέφεται κυρίως σε διαταραχές που συναντάμε συχνότερα στην παιδική και εφηβική ηλικία, όπως είναι αυτές της συμπεριφοράς, της διάθεσης, της ΔΕΠΥ (Fennig & Carlson 1995, Hibbs et al 1991, Peris & Baker 2000, Seifer 1992, Schwartz 1990, Vostanis et al 1994, Vostanis & Nicholls 1992. Επίσης, η έρευνα στον παιδικό και εφηβικό πληθυσμό φαίνεται να ενδιαφέρεται περισσότερο για την επίπτωση του μητρικού ΕΣ στην ψυχική υγεία του παιδιού και όχι τόσο για τον συσχετισμό του με τις υποτροπές μιας ψυχιατρικής διαταραχής, όπως συμβαίνει στους ενηλίκους ασθενείς με εγκατεστημένη ψυχοπαθολογία.…”
Section: το ες σε ερευνητικες μελετες με οικογένειες παιδιων και εφηβων ασθενώνunclassified
“…Τα αποτελέσματά τους έδειξαν ότι ο συσχετισμός μεταξύ ΕΑ και έκβασης ήταν υψηλότερος από τον συσχετισμό ΕΣ και έκβασης, και ότι η ΕΑ αποδείχτηκε πιο ανθεκτική στις ψυχοκοινωνικές παρεμβάσεις απ' ό,τι το ΕΣ. Οι Ramsauer et al (2012) διαπίστωσαν ότι οι έφηβοι, και ιδιαίτερα οι σχιζοφρενικοί έφηβοι, εμφανίζουν σε μεγαλύτερο βαθμό μια στάση αποστροφής του κεφαλιού όταν επικοινωνούν με πρόσωπα φροντίδας υψηλού ΕΣ.…”
Section: ες γονέων και ψυχικες διαταραχες παιδιων και εφηβωνunclassified